A case of a colocutaneous fistula: A rare complication of mesh migration into the sigmoid colon after open tension-free hernia repair. (2015) - Al-Subaie, Saud; Al-Haddad, Mohanned; Al-Yaqout, Wadha; Al-Hajeri, Mufarrej; Claus, Christiano
Highlights: This is the first report of mesh migration to sigmoid colon post tension free hernia repair. Colonoscopy is highly recommended if mesh migration to the colon is suspected. Identification of a concurrent sliding hernia in Lichtenstein repair is adviced to avoid physical contact of a mesh to the sliding organ. Abstract: Introduction: The Lichtenstein technique is commonly used in inguinal hernia repair and a polypropylene mesh is the most frequently used mesh. Mesh migration into the colon has been rarely reported in the literature. Here we report a case of a colocutaneous fistula that developed following delayed mesh migration into the sigmoid colon. Presentation of case: A 52-year-old man undergone Lichtenstein repair for left direct inguinal herniain 2008. Three years later, he presented complaining of rectal bleeding and concurrent bloody discharge from the hernia repair scar. Colonoscopy identified an internal fistulous orifice with intraluminal extrusion of the polypropylene mesh. Furthermore, abdominal ultrasound revealed a fistulous tract extending from the sigmoid colon to the anterior abdominal wall, and a fistulogram confirmed the findings. Open sigmoidectomy and resection of the abdominal wall with the fistula tract was performed, and BIO-A ® tissue reinforcement meshwas placed. His postoperative course was unremarkable and was discharged on postoperative day 3. Discussion: Mesh migration after mesh inguinal hernia repair is unpredictable. A previous report has presented complications related to prosthetics in hernia repair, such as infection, contraction, rejection, and, rarely, mesh migration.Mesh migration may occur as an early or late complication after hernioplasty. Conclusion: During hernia repair, the surgeon should carefully check for a sliding hernia, which may contain the sigmoid colon within the sac, because failure to identify this hernia may lead to direct contact between the mesh and the colon, which may cause pressure necrosis and fistula formation followed by mesh migration.